Wheat Improvement, Management and Utilization 2017
DOI: 10.5772/67274
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Soil Beneficial Bacteria in Wheat Production: A Review

Abstract: Free-living plant growth-promoting rhizobacteria (PGPR) have favourable effect on plant growth, tolerance against stresses and are considered as a promising alternative to inorganic fertilizer for promoting plant growth, yield and quality. PGPR colonize at the plant root, increase germination rates, promote root growth, yield, leaf area, chlorophyll content, nitrogen content, protein content, tolerance to drought, shoot and root weight, and delayed leaf senescence. Several important bacterial characteristics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 184 publications
(199 reference statements)
4
10
0
8
Order By: Relevance
“…Priming of seeds with beneficial bacterial inoculums is an attractive ecological approach to improving germination rates under adverse environmental stress conditions, and to activate plant defense mechanisms at the early stages of plant development due to induced tolerance [ 7 , 8 , 9 , 34 , 35 , 36 , 37 , 38 , 39 ]. Priming affects multiple physiological systems in general, in both seeds and plants and can be defined by the response of primed plants responding to stresses faster and more efficiently [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Priming of seeds with beneficial bacterial inoculums is an attractive ecological approach to improving germination rates under adverse environmental stress conditions, and to activate plant defense mechanisms at the early stages of plant development due to induced tolerance [ 7 , 8 , 9 , 34 , 35 , 36 , 37 , 38 , 39 ]. Priming affects multiple physiological systems in general, in both seeds and plants and can be defined by the response of primed plants responding to stresses faster and more efficiently [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that beneficial bacteria could alleviate the adverse effects of drought on the growth and development of varied plants including wheat [ 1 , 9 , 10 , 16 , 19 , 35 ]. For example, wheat plants inoculated with Azospirillum brasilense Sp245 were characterized by an increase in the linear dimensions of the coleoptile, fresh weight, and an improvement in the indicators of the water status of seedlings in comparison with control samples under drought [ 38 ]. A. brasilense INTA Az-39 increased the yield of wheat grown in dry farming zones due to an increase in the growth rate under the influence of these bacteria, an increase in the level of biomass accumulation, and the number of grains per spikelet [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PGPR are important in agriculture in order to promote the cycling and circulation of plant nutrients, stimulate plant growth, inhibit of plant ethylene synthesis, enhance stress resistance and reduce the need for chemical fertilizers as much as possible. PGPR can colonize near growing roots and use root exudates as a carbon source, affecting plant growth both directly and indirectly through many important bacterial properties, such as nitrogen fixation, production of plant growth hormone and enzymes, solubilisation of inorganic phosphate and mineralization of organic phosphate, 1aminocydopropane-1-carboxylic acid (ACC) deaminase ability, reduction in ethylene levels, nutrient uptake and production of siderophores (Hayat et al, 2010;Liu et al, 2015;Çakmakçı et al, 2017a). Since wrong and repeated overuse of chemical fertilizers has a detrimental effect on soil quality and health by destabilizing soil fertility and soil microbial community structure, interest in PGPR has increased in recent years and its use as biological fertilizers is increasingly common.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, using different PGR to improve EO yield, composition and content, research that will create an opportunity to change and/or improve the composition of some molecules having economic interest gains importance [23]. Several important bacterial characteristics, such as solubilization of inorganic phosphate, biological nitrogen fixation, mineralization of organic matter and solubilization of inorganic phosphate, secretion of certain volatile organic compounds and lowering of plant ethylene level, nutrient uptake, promoting beneficial plant-microbial association, increasing root permeability, production of phytohormones and siderophores, 1-aminocydopropane-1-carboxylic acid deaminase activity, and exhibition of antimicrobial activity against phytopathogenic microorganisms by several mechanisms, can be evaluated as plant growth promotion features and promoted directly or indirectly by many mechanisms such as plant development [23][24][25][26][27][28]. By efficient use, it is expected that PGPR will make contribution to agronomic efficiency, commonly by reducing environmental pollution and costs, by removing the harmful chemicals.…”
Section: Introductionmentioning
confidence: 99%